2020
DOI: 10.1029/2020jd033242
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Comment by E. T. Swenson, D. Das, and J. Shukla on “Unraveling the Mystery of Indian Summer Monsoon Prediction: Improved Estimate of Predictability Limit”

Abstract: (hereafter SN20) raise some technical issues on observed correlations between the synoptic variances and the seasonal mean of area averaged (all-India or central India) Indian summer monsoon rainfall (ISMR) reported in Saha et al. (2019,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…(2021) and S. K. Saha et al. (2019, 2020) study. The same methodology was also used in Swenson et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2021) and S. K. Saha et al. (2019, 2020) study. The same methodology was also used in Swenson et al.…”
Section: Resultsmentioning
confidence: 99%
“…The proper combination of both “autoconversion” coefficients ( C MA and C CA ) can help to encapsulate the synoptic activity (e.g., lows, depression, cyclones, etc. ), which in turn affects the seasonal mean ISMR (S. K. Saha et al., 2020). These are the large rain‐bearing systems (i.e., lows, depressions, and cyclones), which primarily passed through central India (recognized as a homogeneous rainfall region) and determines the seasonal accumulated rainfall (Goswami, 1998; Goswami et al., 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies suggest that ISMR may be more predictable than it was thought before (Dwivedi et al, 2015;Saha et al, 2019Saha et al, , 2020. In general, we seek a linear relationship between the predictors and predictand to estimate the signal or predictable component.…”
Section: -60 Days; Sikkamentioning
confidence: 99%
“…The active and break spells are also influenced by the spatial clustering of synoptic activities during ISM (Goswami et al, 2003). Later, Saha et al (2019, 2020, 2021) have also showed that the synoptic variance of rainfall is strongly coupled with mean ISMR and also likely to be predictable due to its association with large‐scale predictors (e.g., ENSO). Ganai et al (2016) have also pointed out that the improved understanding of the parameterization scheme in the CFS model may lead to the proper simulation of observed diurnal variability in active and break phases.…”
Section: Introductionmentioning
confidence: 99%